2004
DOI: 10.1093/condor/106.3.686
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Basis of Ornamental Feather Colors in Male Zebra Finches

Abstract: The carotenoid-pigmented bill of Zebra Finches (Taeniopygia guttata) has received much recent attention as a sexually selected signal of quality, but these birds also display several sexually dichromatic plumage traits, including rust-colored cheek patches, a black breast band, and brown flanks. Black, brown, and earth-toned features in animals are thought to be produced by melanin pigments, but few studies have identified the melanin content of such colors in bird feathers. We used a series of biochemical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The lack of nutritional effects on male cheek development underlines that timing and duration of dietary restrictions matter. Cheek ornamentation is melanin-based containing 99.2% phaemelanin and 0.8% eumelanin [49] and even though its synthesis was recently shown to be affected by dietary manipulations [50] it is considered to be energetically cheap [51]. Our findings expand on these studies by showing that the expression of plumage ornaments is not affected by dietary history, whereas nutritional condition during the actual development of the ornaments affects their expression [52].…”
Section: Discussionsupporting
confidence: 65%
“…The lack of nutritional effects on male cheek development underlines that timing and duration of dietary restrictions matter. Cheek ornamentation is melanin-based containing 99.2% phaemelanin and 0.8% eumelanin [49] and even though its synthesis was recently shown to be affected by dietary manipulations [50] it is considered to be energetically cheap [51]. Our findings expand on these studies by showing that the expression of plumage ornaments is not affected by dietary history, whereas nutritional condition during the actual development of the ornaments affects their expression [52].…”
Section: Discussionsupporting
confidence: 65%
“…Given the large number of studies reporting associations between MC1R genotype and coloration [8] and the fact that the white zebra finch phenotype clearly reflects a lack of melanin [13], we were surprised to find no association between MC1R genotype and plumage colouration. However, our data do not allow us to definitively rule out a role for MC1R , partly because we were unable to recover high quality sequence data for a small portion of the coding region (26/945 bp), but also because substitutions in MC1R regulatory regions could also be involved [8].…”
Section: Discussionmentioning
confidence: 96%
“…A good candidate for further study is the black cheek morph, where the orange cheek patch in the male is instead black and females gain a black cheek patch. This particular trait is limited to a small region of plumage, it can be explained by differences in melanin deposition [13] and its expression is not sex-dependent. It may therefore have a different genetic basis to the white morph since the latter lacks multiple melanin-based ornaments, potentially implicating changes at the regulatory level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the dispersive Raman spectrometer, we used a FT-Raman spectrometer to analyze pheomelanin from feathers (in this case, orange flank feathers from a zebra finch Taenyopigia guttata , as degradative analyses have shown that the color of these feathers is due to the presence of pheomelanin; McGraw and Wakamatsu 2004) and compare the results with those obtained with dispersive Raman. We also analyzed synthetic pheomelanin derived from 5-S-cysteinyldopa (5SCD), the most abundant cysteinyldopa isomer that is formed when cysteine is added to dopaquinone (i.e., the first step of the pheomelanogenesis pathway), synthesized from DOPA (3, 4-dihydroxyphenylalanine) and cysteine using tyrosinase as a natural oxidant following Wakamatsu et al.…”
Section: Methodsmentioning
confidence: 99%